2012
DOI: 10.1002/j.1556-6978.2012.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Motherhood in Counselor Education

Abstract: This phenomenological study examined 20 tenured and nontenured counselor educators regarding their experiences of motherhood and academia. Two central themes from the interviews emerged: environmental influences (including position flexibility, experienced discrimination, and felt support) and choices and circumstances (including defining and establishing boundaries and accepting decisions). Findings are important for understanding academic mothers' experiences and underscore the need for additional research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 26 publications
9
52
0
Order By: Relevance
“…Furthermore, these findings parallel other researchers' findings related to how racial marginalization can affect professional productivity and cause professional neglect (Boehm et al, ; Griffin et al, ; Kern & Grandey, ; Mason & Goulden, ; Philipsen & Bostic, ). The findings also converge with research on counselor educator mothers in the recognition that the work environment influences personal and professional wellness (Hermann et al, ; Stinchfield & Trepal, ; Trepal & Stinchfield, ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, these findings parallel other researchers' findings related to how racial marginalization can affect professional productivity and cause professional neglect (Boehm et al, ; Griffin et al, ; Kern & Grandey, ; Mason & Goulden, ; Philipsen & Bostic, ). The findings also converge with research on counselor educator mothers in the recognition that the work environment influences personal and professional wellness (Hermann et al, ; Stinchfield & Trepal, ; Trepal & Stinchfield, ).…”
Section: Discussionsupporting
confidence: 77%
“…Although there are studies and pertinent findings on African American women in academia (Bradley, ; Evans & Cokley, ) and mothers in counselor education (Herman et al, ; Trepal & Stinchfield, ), some limitations do exist with regard to sample composition (i.e., predominantly White samples), participation recruitment, and participant selection. In addition, none of these studies have specifically explored the intersectionality of African American mothers in counselor education programs and the impact of these identities on their role as a counselor educator.…”
Section: African American Mothers and Academiamentioning
confidence: 99%
“…Mothers of young children do not move into tenure‐track positions at the same rate as other faculty (Morrison et al, ; Wolfinger et al, ); motherhood has been identified as a significant factor in women not earning tenure as often as their male colleagues (Connelly & Ghodsee, ; Ecklund & Lincoln, ). Scholars have identified some of the barriers mothers experience in academia (Morrison et al, ; Wolfinger et al, ; Wolf‐Wendel & Ward, ), including those faced by counselor educator mothers (Hermann, Ziomek‐Daigle, & Dockery, ; Stinchfield & Trepal, ; Trepal & Stinchfield, ). In addition to describing barriers, researchers have highlighted benefits of academic motherhood (Connelly & Ghodsee, ; Hermann et al, ; Trepal & Stinchfield, ; Ward & Wolf‐Wendel, ).…”
mentioning
confidence: 99%
“… Women often face challenges when balancing academic and familial responsibilities (Gilbert, ; Trepal & Stinchfield, ). This phenomenological study explored women's ( N = 10) experiences of becoming mothers during a doctoral program in counseling.…”
mentioning
confidence: 99%